(untitled) (Informatica, 2023)
Regarding the digital transformation of modern technologies, the amount of data increases significantly resulting in novel knowledge discovery techniques in Data Analytic and Data Mining. These data usually consist of noises or non-informative features which affect the analysis results. The features-eliminating approaches have been studied extensively in the past few decades name feature selection. It is a significant preprocessing step of the mining process, which selects only the informative features from the original feature set. These selected features improve the learning model efficiency. This study proposes a forward sequential feature selection method called Forward Selection with Genetic Algorithm (FS-GA). FS-GA consists of three major steps. First, it creates the preliminarily selected subsets. Second, it provides an improvement on the previous subsets. Third, it optimizes the selected subset using the genetic algorithm. Hence, it maximizes the classification accuracy during the feature addition. We performed experiments based on ten standard UCI datasets using three popular classification models including the Decision Tree, Naive Bayes, and K-Nearest Neighbour classifiers. The results are compared with the state-of-the-art methods. FS-GA has shown the best results against the other sequential forward selection methods for all the tested datasets with O(n2) time complexity.